Implementing Inclusive Pedagogy in Islamic Religious Education (PAI): Strategies for Classroom Management at SMPIT Al Uswah Bangil - Romlah, Siti; Makhzuniyah, Minhah (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2025)
This study examines the implementation of inclusive Islamic Religious Education (PAI)at SMPIT Al Uswah Bangil, focusing on strategies that integrate students with specialneeds into regular classrooms. The research highlights the school’s adaptive approach,combining modified lesson plans, flexible teaching methods (lectures, Q&A,demonstrations, and technology), and strategic classroom management to ensureequitable learning. Key findings reveal that personalized instruction, peercollaboration, and supportive teacher-student relationships enhance participation andcomprehension for all learners. While assessments follow the standard curriculum,accommodations are made to address diverse abilities. The study also underscores theeffectiveness of faith-based interventions, such as Quranic therapy and reward-penaltysystems, in supporting students with special needs. Ultimately, the findings advocatefor stronger institutional commitment to inclusive education, backed by parentalinvolvement and policy reforms, affirming education as a universal right that mustcater to every learner’s unique potential.